Pendidikan Keimanan Kepada al-Qur'an dalam Perspektif Surah Al-baqarah ayat 2 dan Surah Yunus Ayat 57 - Sayuti, Muhammad; Ariyanto; Abbas , Firhat (Indra institute Research & Publication, 2023)
This article discusses the education of faith in the Al-Quran from the perspective of the Al-Quran itself by observing the words of Allah SWT in surah Al-Baqarah verse 2 and surah Yunus verse 57 through the interpretation of two mufassir, namely Ibnu Kathir and Quraish Shihab, as well as the values ​​contained in them. inside it. This article uses a descriptive method. The Tafsir Almisbah and Tafsir Ibn Kathir are the main sources for this article. Literature deemed relevant to this article as secondary sources. This article reveals that the education of faith in the Al-Quran contained in Surah Al-Baqarah verse 2 and Surah Yunus verse 57 contains education, guidance, medicine and is a blessing for believers.